A novel strategy to immobilize bacteria on polymer particles for efficient adsorption and biodegradation of soluble organics. Issue 32 (2nd August 2017) - Cai, Yahui; Yang, Shun; Chen, Dongyun; Li, Najun; Xu, Qingfeng; Li, Hua; He, Jinghui; Lu, Jianmei
Abstract : A novel strategy was used to immobilize bacterial cells on the surface of functional polymer particles for the efficient adsorption and biodegradation of organics in wastewater. Abstract : A novel strategy was used to immobilize bacterial cells on the surface of functional polymer particles for the efficient adsorption and biodegradation of organics in wastewater. First, the bacterial cells were aggregated using a vinyl-containing pre-polymer, and the obtained bacteria–pre-polymer complex was then used as a particle stabilizer to construct a stable Pickering emulsion of functional cross-linking monomers and hydrophobic superparamagnetic iron oxide nanoparticles (the oil phase) in water. After polymerization, the bacteria–pre-polymer complex was covalently fixed to the surface of the polymer particles. Two species of bacterial cells ( Pseudomonas putida and Paracoccus denitrificans ) were used as models to study their removal capacity for phenol and DMF, respectively. Batch experiments showed that the as-prepared magnetic bacteria–polymer (MPB) composites could efficiently remove organics from the aqueous solutions, and the encapsulated iron oxide nanoparticles enabled the MPB composites to be magnetically separated.